Occupational safety and health hazards among artisanal and small-scale gold miners at Mazowe Jumbo Mine, Zimbabwe: A mixed-methods cross-sectional study - Bridget Nyamombe; Vincent Itai Tanyanyiwa (Public Health and Occupational Safety Journal, 2025)
Background: Artisanal and small-scale gold mining (ASGM) is associated with multiple occupational hazards that artisans are often unaware of. Objectives: To identify the occupational hazards and risk factors among artisanal gold miners at Mazowe Jumbo mine, Zimbabwe. Methods: The cross-sectional study employed Mixed-methods(Sep- Nov 2023). Purposive sampling of 34 miners from two sites (response rate was 100%). The interview was administered using questionnaires, structured interviews, field observations, and document review. Quantitative data were analyzed descriptively (frequencies and proportions), and qualitative data underwent thematic analysis. Results: Heavy lifting was reported by 100% (34/34), manual handling by 91.2% (31/34), silica dust exposure by 91.2% (31/34), and contaminated water by 85.3% (29/34). Key risk factors included lack of PPE, financial pressure, and low OSH awareness. Field observations noted unsecured shafts, poor sanitation, and evidence of substance use on site. Conclusions: ASG miners at Mazowe Jumbo Mine face multi-domain OSH hazards. We recommend targeted OSH training programmes, provision of PPE, improved sanitation, and monitoring/ formalization of ASGM activities.